2023
DOI: 10.1039/d3tc01444d
|View full text |Cite
|
Sign up to set email alerts
|

Decoding intrinsic and extrinsic contributions for high piezoelectricity of CBT-based piezoelectric ceramics

Abstract: The excellent electrical properties of CaBi4Ti4O15 -based piezoelectric ceramics come from both of intrinsic and extrinsic contributions. Nb5+/Mg2+ co-doping into the Ca0.6(Na0.5Bi0.5)0.4Bi4Ti4O15 ceramic results in the increased oxygen octahedron tilts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…5(e)–(g) illustrates a comparison of d 33 , ρ dc , and T C between some reported bismuth-layered structure ceramics and the LTO-based ceramics in this work. 16,17,23 The d 33 of modified bismuth layered structure ceramics consistently surpasses the LTO-LC3 ceramics. However, the ρ dc value of the bismuth layered structure materials remains below 10 6 Ω cm at 700 °C.…”
Section: Resultsmentioning
confidence: 97%
“…5(e)–(g) illustrates a comparison of d 33 , ρ dc , and T C between some reported bismuth-layered structure ceramics and the LTO-based ceramics in this work. 16,17,23 The d 33 of modified bismuth layered structure ceramics consistently surpasses the LTO-LC3 ceramics. However, the ρ dc value of the bismuth layered structure materials remains below 10 6 Ω cm at 700 °C.…”
Section: Resultsmentioning
confidence: 97%
“…Bismuth layer-structured ferroelectric (BLSF) ceramics with high Curie temperatures (>500 • C) and good thermal stability have great potential in high-temperature piezoelectric sensor applications. Therefore, BLSF ceramics such as CaBi 2 Nb 2 O 9 (Tc ∼ 940 • C, d 33 ∼ 5 pC/N) [3], CaBi 4 Ti 4 O 15 (Tc ∼ 790 • C, d 33 ∼ 9 pC/N) [4], Na 0.5 Bi 4.5 Ti 4 O 15 (Tc ∼ 660 • C, d 33 ∼ 17 pC/N) [5], and Bi 4 Ti 3 O 12 (Tc ∼ 675 • C, d 33 ∼ 6 pC/N) [6,7] have drawn great attention in recent years. Among them, CaBi 4 Ti 4 O 15 (CBT) is often considered a good candidate for high-temperature piezoelectric materials because of its good comprehensive properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BLSF ceramics such as CaBi 2 Nb 2 O 9 (Tc ∼ 940 • C, d 33 ∼ 5 pC/N) [3], CaBi 4 Ti 4 O 15 (Tc ∼ 790 • C, d 33 ∼ 9 pC/N) [4], Na 0.5 Bi 4.5 Ti 4 O 15 (Tc ∼ 660 • C, d 33 ∼ 17 pC/N) [5], and Bi 4 Ti 3 O 12 (Tc ∼ 675 • C, d 33 ∼ 6 pC/N) [6,7] have drawn great attention in recent years. Among them, CaBi 4 Ti 4 O 15 (CBT) is often considered a good candidate for high-temperature piezoelectric materials because of its good comprehensive properties [4]. However, the piezoelectric constant of pure CBT is relatively low (∼9 pC/N), limiting its practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various previous studies have focused on this method, and some achievements had been realized. 13,14 Wu et al 15 revealed that CBT ceramics doped with Bi 4 Ti 3 O 12 exhibit an optimal piezoelectric constant (d 33 = 13 pC/N). Liu et al 16 reported that Ta/Mn co-doped CBT ceramics exhibit improved electrical properties (d 33 = 24.0 pC/N, T c = 793 1 and Figure S1.…”
Section: Introductionmentioning
confidence: 99%